Translating Pancasila in Global Justice Context: Does it matter? - Arifin, Ridwan (Indonesian Journal of Pancasila and Global Constitutionalism, 2024)
Pancasila, the philosophical foundation of the Indonesian state, encapsulates the principles of justice, humanity, and social harmony. However, as the world becomes increasingly interconnected, questions arise regarding the relevance and translatability of Pancasila in the global context of justice. This paper explores the significance of translating Pancasila's principles into global justice frameworks, examining its implications and challenges. Drawing on philosophical, legal, and sociopolitical perspectives, this paper argues that while Pancasila offers valuable insights into justice, its translation into global contexts requires careful consideration of cultural, political, and ethical nuances. Through comparative analysis and case studies, this paper investigates the feasibility and desirability of integrating Pancasila into global justice discourses, shedding light on the potential contributions and limitations of cross-cultural ethical frameworks.